Milk Productivity of Crossbreed Generation Received from Black and White and Golshtin Breeds (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents information about crossbreed generation received from black and white and golshtin breeds, milk productivity of cows during the lactation in each month, fat indicators of milk and fat expenses.